Quantifying the breadth of antibiotic exposure in sepsis and suspected infection using spectrum scores. Issue 41 (14th October 2022) - Smith, Joshua T.; Manickam, Raj N.; Barreda, Fernando; Greene, John D.; Bhimarao, Meghana; Pogue, Jason; Jones, Makoto; Myers, Laura; Prescott, Hallie C.; Liu, Vincent X.
Abstract : A retrospective cohort study. Studies to quantify the breadth of antibiotic exposure across populations remain limited. Therefore, we applied a validated method to describe the breadth of antimicrobial coverage in a multicenter cohort of patients with suspected infection and sepsis. We conducted a retrospective cohort study across 21 hospitals within an integrated healthcare delivery system of patients admitted to the hospital through the ED with suspected infection or sepsis and receiving antibiotics during hospitalization from January 1, 2012, to December 31, 2017. We quantified the breadth of antimicrobial coverage using the Spectrum Score, a numerical score from 0 to 64, in patients with suspected infection and sepsis using electronic health record data. Of 364, 506 hospital admissions through the emergency department, we identified 159, 004 (43.6%) with suspected infection and 205, 502 (56.4%) with sepsis. Inpatient mortality was higher among those with sepsis compared to those with suspected infection (8.4% vs 1.2%; P < .001). Patients with sepsis had higher median global Spectrum Scores (43.8 [interquartile range IQR 32.0–49.5] vs 43.5 [IQR 26.8–47.2]; P < .001) and additive Spectrum Scores (114.0 [IQR 57.0–204.5] vs 87.5 [IQR 45.0–144.8]; P < .001) compared to those with suspected infection. Increased Spectrum Scores were associated with inpatient mortality, even after covariate adjustments (adjusted odds ratio per 10-point increase in Spectrum Score 1.31; 95%CI 1.29–1.33). Spectrum Scores quantify the variability in antibiotic breadth among individual patients, between suspected infection and sepsis populations, over the course of hospitalization, and across infection sources. They may play a key role in quantifying the variation in antibiotic prescribing in patients with suspected infection and sepsis.